Spatial distribution and characteristics of Andean ice masses in Argentina: Results from the first National Glacier Inventory - Zalazar, Laura Viviana (2020)
Glaciers and the periglacial environment in Argentina have been protected by the Law since 2010. This legislation required the development of the first National Glacier Inventory (NGI), which was officially presented in May 2018 and based on satellite images spanning between 2004 and 2016. Here, we present the methods and results of the NGI, summarize the glaciers' morphological and spatial characteristics, and compare our results to previous regional and global inventories. The NGI reveals an impressive variety of ice masses including rock glaciers, permanent snowfields, mountain and valley glaciers with varying amounts of debris-cover and large outlet glaciers. The Argentinean Andes contain 16 078 ice masses covering an area of 5769 kmbetween 200 and 6900 m a.s.l. Comparison of the combined national inventories of Argentina and Chile (~30 000 glaciers and 28 400 km2) with the Randolph Glacier Inventory 6.0 for the Southern Andes (~16 000 glaciers and 29 400 km2), shows that there are large differences in extent and number of glaciers in some sub-regions. The NGI represents an improvement for a better understanding of Argentina's freshwater reservoirs and provides detailed information for the preservation and study of ice masses along 4000 km of the Southern Andes.